STUDY OF NaOH - ACTIVATION TEMPERATURE INFLUENCE TOWARD CHARACTER OF MESOPOROUS CARBON BASED ON TEXTILE SLUDGE WASTE - Tutik Setianingsih; Uswatun Hasanah; Darjito Darjito (Universitas Gadjah Mada, 2008)
Textile sludge waste contains many organic matters so that it is potential to be used as mesoporous carbon precursor. Actived carbon with mesopore character is effective as adsorbent and catalyst carrier of large molecules. Synthesis of the activated mesoporous carbon was done with purpose to study influence of activation temperature toward characters of the carbon. Process of the synthesis involved dry sludge (50 g) as precursor, concentrated sodium silicate solution SiO2 24.5% and Na2O 7.5% (50 mL) as template source, 1 M HCl solution (50 mL) as polimering agent, carbonization condition at 600 °C 3 h under nitrogen gas flow, activation conditions with NaOH 50% and various temperatures (400, 500, 600, 700, and 800 °C), and demineralizatin conditions with 0.1 M HCl solution for 4 h and 125 rpm. All of the products were characterized with methylen blue method to determine specific pore volume and specific surface area. The carbon obtained at optimum temperature was characterized again with surface area analyzer. Result of the research showed that the optimum condition was achieved at activation temperature of 500 °C. Characters of the synthesized carbon at the optimum condition were specific surface area of 638.32 m2/g, specific pore volume of 0.35 cm3/g, average pore diameter of 21.78 Å, and methylene blue number of 358.87 mg/g.